Simulation and Analysis of Lightning Backflashover for the 132 Kv Kuala Krai–Gua Musang Transmission Line Using PSCAD - Sardi, Junainah (2009)
Lightning has been a major concern to the power system researchers as it may cause damage to the connected electrical equipment especially to the transmission line. One of the event that will cause lightning overvoltage and most likely to occur is backflashover. For that reason, one study has been carried out where values of backflashover rate (BFR) on a transmission line and probability of transformer damage at substation are observed due to backflashover. A sample of worst performance of transmission line in Peninsular Malaysia i.e. 132 kV Kuala Krai-Gua Musang transmission line data was obtained from Tenaga Nasional Berhad (TNB) for the purpose of backflashover analysis. Power System Computer Aided Design, PSCAD software was used to model integral part of transmission line components such as insulator gap, tower and footing resistance followed by doing the backflashover simulation and analysis. Besides that, the effects of line parameters such as ground resistance, soil resistivity, tower surge impedance, tower height and number of shield wires in lightning performance study were also investigated. Findings from backflashover analysis of Kuala Krai-Gua Musang transmission line using PSCAD imply that the values of backflashover rate (BFR) and probability of transformer damage are influenced by the values of line parameters. Right selection of line parameters may reduce BFR and probability of transformer damage, thus improve the transmission line performance. Findings of this research can be useful guideline towards high voltage transmission line design and planning in Malaysia.